Exploring the Impact of Iron Deficiency Anaemia on Glycated Haemoglobin A1c Levels in Pregnant and Non-Pregnant Women: A Systematic Review - AlQarni AM; Alghamdi AA; Aljubran HJ; Bamalan OA; Abuzaid AH; AlYahya MA; AlAwami AM; Al Shubbar MD; Al Yousif GF (Dove Medical Press, 2024)
Amani M AlQarni,1 Amal A Alghamdi,1 Hussain J Aljubran,2 Omar A Bamalan,2 Abdullah H Abuzaid,2 Mohammed A AlYahya,2 Ahmed M AlAwami,2 Mohammed D Al Shubbar,2 Ghada F Al Yousif1 1Department of Family and Community Medicine, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 2College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Amani M AlQarni, Family and community medicine department, King Fahd Hospital of the University, Imam Abdulrahman bin Faisal University, Dammam, 34212, Saudi Arabia, Tel +966133333766 ; +966591775751, Email Amqurni@iau.edu.saAbstract: Haemoglobin A1C (HbA1c) is fundamental in monitoring glycaemic control during pregnancy. However, several conditions could affect this test's accuracy, including iron deficiency anaemia (IDA). Hence, this systematic review delves into the underexplored connection between IDA, iron replacement therapy (IRT), and haemoglobin A1C (HbA1c) during pregnancy. An electronic search of the Cochrane, MEDLINE, and Embase databases was conducted by six authors. From a comprehensive search strategy, 968 records were obtained. After applying the inclusion and exclusion criteria, seven studies were included, comprising 365 women selected for analysis. Six studies indicated a positive correlation between IDA and HbA1c levels, while one found no correlation. The average HbA1c level of the included studies in pregnant women was 5.64%. In comparison, it was found that non-pregnant women had lower HbA1c levels. Among the included studies, the mean HbA1c levels decreased from 5.1% to 4.89% after treating pregnant women with IRT. The review emphasises the complexity of interpreting HbA1c levels in pregnant women with IDA, highlighting the influence of pregnancy-induced physiological changes. In addition, this suggests that HbA1c should not be the sole criterion for diabetes management in pregnant women with IDA. Future research should focus on alternative glycaemic monitoring methods unaffected by IDA.Keywords: iron deficiency anaemia, iron replacement therapy, pregnancy, gestational diabetes, glycated haemoglobin, HbA1c